Indonesia sebagai Poros Maritim Dunia - Dwi Ardiyanti (Department of Political Science - Universitas Sains Al-Qur’an, 2018)
With its potential wealth in the sea and its position in the international business sea-line, Indonesia should display the maritime strength. Jokowi’s vision to make Indonesia one of the maritime axis in the world has been embodied clearly by the Ministry of Maritime Affairs and Fisheries. Yet, the challenge and opportunities to become international maritime axis should be handled appropriately. Located in international business transit between Pacific and Indian Ocean, Indonesia is prone to criminals of drugs smuggling from/to Indonesia as well as the asylum seekers. This research attempts to analyze the Indonesia’s challenges and opportunities in Jokowi’s era with his vision to become the international maritime axis.